PENGARUH LAPISAN PENYANGGA PRBA2CU3O7-? PADA FILM TIPIS SUPERKONDUKTOR YBA2CU3O7-? - Saragih (NIM : 20296506), Horasdia
Abstract : The thin film YBa2Cu3O7-? with buffer layer PrBa2Cu3O7-? on substrate MgO (100) have successful fabricated by using On-axis unbalanced dc magnetron sputtering method. The deposit thin film was characterized by X-ray diffraction, p-T measuring and Scanning electron microscopy. The X-ray diffraction analysis result the volume fraction of PrBa2Cu3O7-?/MgO(100), YBa2Cu3O7-?/MgO(100), YBa2Cu3O7-?/ PrBa2Cu3O7-?/MgO(100) (film-I), and YBa2Cu3O7-?/PrBa2Cu3O7-?/ MgO(100) (film-II) was 79,84%, 69,01%, 57,23% and 65,54% respectively. The using buffer layer PrBa2Cu3O7-? will decrease the volume fraction of the thin film superconductor YBa2Cu3O7-?, however the volume fraction will increase by increasing of the thickness of the buffer layer PrBa2Cu3O7-?. Present of the buffer layer affect the increasing of the critical temperature of the thin film superconductor YBa2Cu3O7-? as well as increasing of the thickness of the buffer layer PrBa2Cu3O7-?